SIMULATING WATER BALANCE AND CROP YIELD FOR SUGARCANE PLANTATION IN PASURUAN USING AQUACROP MODEL - Andre Dani Mawardhi (OISAA, 2022)
Sugarcane is one of the estate crops that has been cultivated in Indonesia for a long time. Sugarcane farmers must be more adaptable and adjust their current field management as a result of water shortage caused by climate change. rip irrigation has been one of the prospectus alternatives to be implemented by farmers by altering their furrow irrigation. Before being implemented in the field, the AquaCrop model is useful to simulate the advisability of particular farm management such as irrigation. The AquaCrop model was used to simulate and analyse the water balance, crop yields, and water productivity of sugarcane in Pasuruan under two alternative field managements, i.e. conventional and enhanced practices. Results confirmed that drip irrigation requires less water for irrigation than furrow irrigation. In comparison to no mulching procedures in conventional method, improved field management decreased surface run-off by up to 95%. Farmers obtained higher crop yield and water productivity by shifting the farm management, i.e. 7-8% and 12-16%, respectively. However, there are several constraints on this analysis. Thus, advanced studies on conducting AquaCrop for more realistic conditions are still promising in future.